Identifikasi zona lemah pada ruas Jalan utama Ajibarang – Gumelar kabupaten Banyumas menggunakan metode geolistrik resistivitas - Sehah Sehah; Tita Murwiyanti; Sukmaji Anom Raharjo (Universitas Jenderal Soedirman, 2020)
Research using the geoelectric-resistivity method with Wenner configuration has been carried out to identify the subsurface rock structures especially weak zones on the part of main road of Ajibarang – Gumelar, Ajibarang District, Banyumas Regency. Resistivity data acquisition has been carried out on two trajectories with a length of each trajectory is 200 meters. The data acquired are the apparent resistivity values of subsurface rocks. The modeling results of apparent resistivity values in inversion have produced a two-dimensional (2D) cross section of subsurface rock resistivity. The interpretation results of the resistivity cross section have shown three layers of subsurface rocks consisting of fine to moderate grained sandstone with a resistivity value of 2.37 – 6.56 Ωm, limely marl with a resistivity value of 6.32 – 12.60 Ωm, and limestone with a resistivity value of 12.10 – 24.30 Ωm. The results of lithological interpretation of the resistivity cross section have shown the existence of a weak zone in this area at the measurement point about of 140 – 180 meters. The weak zone is interpreted as limestones and sandstones which have fine to moderate grain that is soft and not compact